POLITIK DESENTRALISASI FISKAL: PERMASALAHAN DALAM IMPLEMENTASI - Juli Panglima Saragih (Sekretariat Jenderal DPR RI, 2014)
Fiscal decentralization is a fiscal policy taken by government to balance inequality fiscal capacity between local-central governments, as well as amongst local government. By concept or formula, it is fairly accepted as a good model of fiscal policy. This research applies a qualitative method that aims to analyse its implementation, particularly problems faced by local budgets, namely its low capacity to cover the increase of local development needs. Relevant secondary data is used to analyse the implementation of fiscal decentralization as a fiscal policy in general. This research concludes that as a concept, fiscal decentralization is a good policy of decentralization, in term of politics. However, due to local budget constraints faced by regional governments, its implementation still meets problems, such as less of local revenue capacity that causes deep dependency on national budget transfer. Also, local tax policy cannot significantly help to solve local budget problems until now.